TEENAGER’S FASHION IN HO CHI MINH CITY: NEW TRENDS AND ISSUES - Nguyen, TNH (Proceeding of the International Conference on Arts and Humanities, 2023)
Thanks to the favorable geographical position for trade and economic development, the urbanization process in Ho Chi Minh City took place early and quickly. Modern media have boosted social development in all aspects, such as literacy levels, information exchange, communication, community activities, and particularly greater awareness of prevailing trends in beauty, fashion, music, movies, painting and numerous related aspects. Therefore, this not only creates great opportunities but also poses challenges to the country. Adolescents are significantly influenced by these changes as they desire to assert their own character and identity. Teenagers’ dressing up like their idols or celebrities has become a growing trend. This has created a multi-colored identity for the fashion industry, signifying art and humanity and effecting both positive and negative changes in the costume culture. Through synthesized and analyzed data, this research presented a systematic review on the costumes of young people in Ho Chi Minh City and highlight the key factors that influence fashion trends among them. In addition, detailed comments and aesthetic orientations were made to contribute to building costume culture and improving fashion taste for young people in Ho Chi Minh City in particular and in Vietnam general.